STRUKTUR DAN KINERJA INDUSTRI BESI DAN BAJA INDONESIA TIDAK SEKUAT DAN SEKOKOH NAMANYA - Prasetyo, P. Eko (JEJAK: Jurnal Ekonomi dan Kebijakan, 2010)
The existence of iron and steel industry occupy vital role in the development process and become strategically for the progress of a nation, because almost all metal equipment that are used by people made of steel. This research is aim to study structure and performance also competitive power of Indonesian national iron and steel industry that is below the note and not as firm as the name. This study endured by the way of literature research based from the primary data of BPS during the last five years that was since years 2004 until the beginning of year 2010. Based on the result of the research it is concluded that structure and performance of Indonesian iron and steel industry are still weak contradictive. The main reason that faced by this industry is the high import dependencies of raw material, especially at head steel industry. The low level of consumption per capita that at 33 kg per capita cannot be fulfilled by the level of national production that always under the level of the consumption, with the result that this lag must be fulfilled with import. The next consequence, national iron and industry are not become standalone and low at competition power, with the result that the problem of consumption that always be bigger than the production become more dependent at the condition of world iron and steel market. Because the lack of raw material, and the international price of raw material highly increased. In the other side, the chaos at the industry cannot be released from the uncertain policy of the government during the time, with the result that national iron and steel industryâs structure canât stand alone and their competitive power are low. For that reason, investment policy to support this industry and local resource wielding are very strategic opportunity to build self-employment and performance of iron and steel industry competitive power including related industry and the lower atIndonesiarecently and the future.Â